Catalysis/CO2 sorption enhanced pyrolysis-gasification of biomass for H2-rich gas production: Effects of activated carbon, NiO active component and calcined dolomite. (15th February 2023) - Li, Bin; Magoua Mbeugang, Christian Fabrice; Xie, Xing; Wei, Juntao; Zhang, Shihong; Zhang, Lei; El Samahy, Adel A.; Xu, Deliang; Wang, Qian; Zhang, Shu; Liu, Dongjing
Highlights: Effects of AC, NiO and calcined dolomite on H2 -rich gas production were studied. AC greatly enhanced gas production due to its catalytic effect and self-gasification. PAC with lower impregnation ratio showed better performance in the process than ZAC. NiO loading on AC further improved H2 production but inhibited AC self-gasification. Big synergistic strengthening effect existed between NiO/PAC-SD and calcined dolomite. Abstract: This study aims to reveal the effects of activated carbon (AC), NiO active component and calcined dolomite addition on the H2 -rich gas production from pyrolysis-gasification of biomass, the experiments were conducted on a two-staged fixed-bed reactor with sawdust (SD) as biomass feedstock. It was found that the H2 -rich gas production was largely enhanced by AC catalyst due to its catalytic effect on volatiles gasification as well as its self-gasification during the process. Lower impregnation ratio of ZnCl2 or H3 PO4 to biomass was preferable to the H2 production. H3 PO4 activation char (PAC) might keep more active structures with higher AC yields compared with ZnCl2 activation char (ZAC). NiO would mainly enter into the micropores of AC, possibly covered some of the active sites on AC surface, thus caused the decrease in AC self-gasification, although certain catalytic effect of NiO on H2 production was also observed. Additional calcined dolomite introduction together with NiO/AC catalyst could further increase the H2 concentration and yield. A remarkable synergistic strengthening effect was found between NiO/PAC-SD catalyst and calcined dolomite, the maximum H2 concentration and yield of 62.54 vol% and 1343.52 mL/g biomass were achieved with the addition of NiO/PAC-SD-1 and calcined dolomite due to the combination of in situ CO2 sorption enhancing effect and NiO/PAC-SD-1 catalytic effect as well as the enhanced AC self-gasification. It is thus illustrated that the catalysis/sorption enhanced pyrolysis-gasification of biomass using NiO/AC catalyst and calcined dolomite is an effective way to produce a H2 -rich gas and shows a good prospect in the carbon-constrained future.